PENGARUH PEMBELAJARAN ILMU GIZI DAN PERENCANAAN MENU TERHADAP HASIL BELAJAR KREATIVITAS MENU MAHASISWA PROGRAM STUDI TATA BOGA - Ratnawati T; Slamet Widodo; Syamsuriah, Syamsuriah; Ismi Irfiyanti Fachruddin (Nusantara Hasana Journal, 2025)
This study examines the relationship between nutrition knowledge and menu creativity among culinary arts students. Nutrition knowledge is a fundamental competency for culinary professionals, while menu creativity is essential for innovation in the culinary industry. This quantitative research employed correlational design involving 50 culinary arts students selected through purposive sampling. Data were collected using a nutrition knowledge test (30 multiple- choice questions) and menu creativity assessment rubric (5 dimensions: originality, variety, presentation, nutritional balance, and innovation). Data were analyzed using Pearson correlation and simple linear regression. Results showed a significant positive correlation between nutrition knowledge and menu creativity (r = 0.687, p < 0.001), indicating that higher nutrition knowledge is associated with greater menu creativity. Regression analysis revealed that nutrition knowledge contributes 47.2% to menu creativity variance (R² = 0.472). These findings suggest that strengthening nutrition education in culinary curriculum can enhance students’ creative capabilities in menu development. Recommendations include integrating nutrition courses with menu planning practicum and developing project-based learning that combines nutritional principles with culinary creativity.